Nandus prolixus, a new species of leaf fish from northeastern Borneo (Teleostei: Perciformes: Nandidae) - Chakrabarty, Prosanta; Oldfield, Ronald G.; Ng, Heok H. (Zootaxa, 2006)
Nandus prolixus sp. nov. is described from the Sepilok River drainage in Sabah, northeastern Borneo. This species is distinguished from its only Sundaic southeastern Asian congener, N. nebulosus, in having a longer, more produced snout (25.7–30.6% HL vs. 18.5–26.1), more lateralline scales (33–37 vs. 24–34), more scales below the lateral line (12 vs. 10–11), fewer spines in the dorsal fin (XIV vs. XV–XVI), and fewer pectoral-fin rays (15–16 vs. 17–19). It differs from N. nandus (from India) in having fewer lateral-line scales (33–37 vs. 42–55), fewer scales above the lateral line (4–5 vs. 6–7), fewer scales below the lateral line (12 vs. 14–18), more dorsal spines (XIV vs. XII–XIII), and the absence (vs. presence) of a distinct dark spot at the base of the caudal peduncle. It differs from N. oxyrhynchus (from mainland southeastern Asia) in having a more slender body (body depth 37.6–40.5% SL vs. 41.3–44.1) and a less steeply sloping predorsal profile.